2002
DOI: 10.1093/geront/42.6.727
|View full text |Cite
|
Sign up to set email alerts
|

Successful Aging and Well-Being

Abstract: Understanding criteria used by older persons to assess their own successful aging should enhance the conceptualization and measurement of this elusive concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
163
1
15

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 534 publications
(193 citation statements)
references
References 23 publications
14
163
1
15
Order By: Relevance
“…Our findings along with several studies found no gender differences in SA [13,23,29]. In contrast, Strawbridge et al [29] found that a substantially higher percentage of women than men met Rowe and Kahn's definition, whereas a Chinese study found that men were more likely to be successful agers [30]. It is well established that though women live longer than men, they are more likely to report health problems and seek medical attention for them [31].…”
Section: Discussionsupporting
confidence: 78%
“…Our findings along with several studies found no gender differences in SA [13,23,29]. In contrast, Strawbridge et al [29] found that a substantially higher percentage of women than men met Rowe and Kahn's definition, whereas a Chinese study found that men were more likely to be successful agers [30]. It is well established that though women live longer than men, they are more likely to report health problems and seek medical attention for them [31].…”
Section: Discussionsupporting
confidence: 78%
“…Esto sugiere la conveniencia de introducir enfoques e instrumentos alternativos en la evaluación de las necesidades de este grupo (Strawbridge & Wallhagen, 2002). En efecto, los adultos mayores encuestados son activos, están conectados, utilizan Internet para distintos propósitos, sus redes sociales con personas están activas y practican la búsqueda de información específica sobre salud en Internet o en otros medios.…”
Section: Discussionunclassified
“…The data came from five waves of the Chinese Longitudinal Healthy Longevity Survey (CLHLS) in 2000, 2002, 2005, 2008. Started in 1998, the CLHLS is a national survey focusing on the oldest-old to investigate the determinants of health and longevity.…”
Section: Study Samplementioning
confidence: 99%
“…For instance, Strawbridge, Wallhagen, and Cohen (2002) reported that half of the older adults aged 65-99 rated themselves as aging successfully, whereas slightly more than one-third of the older adults evaluated themselves as aging unsuccessfully even though they met Rowe and Kahn's criteria. Bowling and Dieppe (2005) showed that when older adults were asked to provide their own definitions of successful aging, they put relatively greater emphasis on social integration and well-being compared to other components in the biomedical model.…”
Section: Introductionmentioning
confidence: 99%